To multiply the polynomials \( (2r - 5)(r + 4) \), we can use the distributive property (also known as the FOIL method for binomials).
-
First, multiply \( 2r \) by \( r \): \[ 2r \cdot r = 2r^2 \]
-
Next, multiply \( 2r \) by \( 4 \): \[ 2r \cdot 4 = 8r \]
-
Now, multiply \( -5 \) by \( r \): \[ -5 \cdot r = -5r \]
-
Lastly, multiply \( -5 \) by \( 4 \): \[ -5 \cdot 4 = -20 \]
Now, we combine all these results: \[ 2r^2 + 8r - 5r - 20 \]
Combine like terms (\( 8r - 5r \)): \[ 2r^2 + 3r - 20 \]
So, the final result is: \[ \boxed{2r^2 + 3r - 20} \]
In the template format you provided, it would be: \[ 2r^2 + 3r - 20 \] Where the coefficients are:
- \( _ = 2 \) (for \( r^2 \))
- \( _ = 3 \) (for \( r \))
- \( _ = -20 \) (constant)